Factors that contribute to trait mindfulness level among hospitalized patients with major depressive disorder - Ji, Cai-Fang; Wu, Guan-Hui; Du, Xiang Dong; Wang, Gui-Xian; Liu, Li-Li; Niu, Mei-E.; Logan, Robert; Kong, Fan-Zhen (Frontiers in Psychiatry, 2023)
Mindfulness training among patients with major depressive disorder (MDD) reduces symptoms, prevents relapse, improves prognosis, and is more efficient for those with a high level of trait mindfulness. Upon hospital admission, 126 MDD patients completed the Beck Depression Inventory (BDI), World Health Organization Quality of Life Brief, Five-Factor Mindfulness Questionnaire (FFMQ), and the Rumination Response Scale (RRS). The 65 patients that scored less than the median of all subjects on the FFMQ were placed into the low mindfulness level (LML) group. The other 61 patients were placed in the high mindfulness level (HML) group. All facet scores were statistically different between the mental health assessment scores of the HML and LML groups except for RRS brooding and FFMQ nonjudgement. Trait mindfulness level exhibited a negative and bidirectional association with MDD severity primarily through the facets of description and aware actions. Trait mindfulness was also related positively with age primarily through the facets of nonreactivity and nonjudgement. Being married is positively associated with trait mindfulness levels primarily through the facet of observation and by an associated increase in perceived quality of life. Mindfulness training prior to MDD diagnosis also associates positively with trait mindfulness level. Hospitalized MDD patients should have their trait mindfulness levels characterized to predict treatment efficiency, help establish a prognosis, and identify mindfulness-related therapeutic targets.